Assessing the Efficiency and Robustness of the Retrofitted Building Envelope Against Climate change. (November 2015) - Nik, Vahid M.; Mata, Erika; Kalagasidis, Angela Sasic
Abstract: Evaluating the performance of retrofitted buildings for future climatic conditions can be a challenging task since different scenarios and uncertainties exist both for retrofitting of buildings and for future climate. This paper evaluates the energy performance of four retrofitting measures – applied to the building envelope – of the residential building stock in Gothenburg, Sweden. The energy efficiency of the measures is evaluated both on long and short terms, while their robustness against climate uncertainties and extreme climatic conditions is studied. The assessment is carried out using a statistical method, which has been developed specifically for this kind of analysis. The considered measures are ranked by looking into their average performance and their variations during different time scales, i.e. from one hour to 20 years. The analysis helps to identify the retrofitting measures with the most efficient and the most reliable performance for future climatic conditions.